A comparative study of the tensile failure of carbon nanotube, Dyneema and carbon fibre tows over six orders of strain rate. (30th August 2020) - Gspann, Thurid S.; Ngern, Nigel H.H.; Kiley, Patrick J.; McKeown, Philip A.; Bulmer, John S.; Windle, Alan H.; Tan, Vincent B.C.; Elliott, James A.
Abstract: Manufacturing carbon nanotube (CNT) fibres on a large scale with properties that are a significant fraction of those measured for individual tubes or smaller bundles is crucial to achieving greater impact in industrial applications. We describe three macrostructured morphologies produced on a laboratory scale: CNT ribbons, ropes and tows, wherein tows are the most suitable for industrial scale-up, comprising a bundled structure of thousands of individual micro-fibres. For each morphology, we present the tensile failure mechanisms and mechanical performance observed over six orders of magnitude of strain rate. The tests were conducted on a conventional Hounsfield tensile tester (10 ─4 to 10 ─1  s ─1 strain rate) and a modified split-Hopkinson tensile bar tester (30–150 s ─1 strain rate). To avoid the problem of clamp failure, we present a novel method of testing loops, rather than uniaxial samples, as-produced from our chemical vapour deposition reactor. For material benchmarking and validation, we also tested unsized carbon fibre (Hexcel AS4) and Dyneema tows (SK25). All materials were used 'dry', i.e. not as a composite, for raw material and structure comparison. We show here that CNT tows exhibit both a mechanical performance and fracture behaviour which combines the ductility of Dyneema with the tenacity of carbon fibre. Graphical abstract: Image 1